Hasil Belajar Siswa pada Pembelajaran PBL dan Inkuiri Terbimbing Berbantuan PhET pada Materi Laju Reaksi - Agnesia Marpaung; Nurfajriani Nurfajriani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Chemistry learning on reaction rates requires a learning model that can improve conceptual understanding and student learning outcomes through active involvement in the learning process. This study aims to determine the differences in student learning outcomes between Problem-Based Learning (PBL) and guided inquiry models assisted by PhET simulations on reaction rates. This study was a quasi-experimental study with a two-group pretest-posttest design. The study population was all eleventh-grade students of SMA Negeri 8 Medan, with a sample of 64 students selected using a purposive sampling technique. The research instrument was a learning outcome test. Data were analyzed using an independent sample t-test assisted by SPSS. The results showed a significant difference in student learning outcomes between the PBL and guided inquiry classes (Sig. 0.000 < 0.05). The average student learning outcome in the PBL class was 80.47, higher than the guided inquiry class at 70.16. Thus, the Problem Based Learning (PBL) model assisted by PhET simulations is more effective in improving student learning outcomes on reaction rates than the guided inquiry model.